POTENSI ANTIDIABETIK EKSTRAK ETANOL DAUN MATOA(Pometia pinnata) PADA TIKUS PUTIH JANTAN - Afriani S; Nadira; Handayani KR; Wirawan W; Afrizal; Tien Wahyu Handayani; Joni Tandi (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Diabetes Mellitus is a metabolic disease characterized by high blood glucose levels which is commonly called hyperglycemia due to lack of insulin secretion. One of the matoa plants (Pometia pinnata) that has been used as a traditional medicine is matoa leaves which are efficacious as diabetes mellitus. The purpose of this study was to determine the secondary metabolite compounds in the ethanol extract of matoa leaves, as well as to determine the potential dose of ethanolic extract of matoa leaves which was effective in reducing blood glucose levels and on the histopathological description of the pancreas of male white rats induced by Streptozotocin. This study used a laboratory experimental method, divided into 6 treatment groups, each group consisting of 5 rats, namely normal control, negative control, positive control, treatment groups with doses of 100, 200, and 300 mg/kg body weight. Data were analyzed using One Way ANOVA statistical test at 95% confidence level followed by LSD test to see differences between treatments. The results showed that the ethanolic extract of matoa leaves contained secondary metabolites of alkaloids, flavonoids, saponins, tannins, and steroids. at a dose of 300 mg/kg BW showed effective results in reducing blood glucose levels with an average decrease of 99.6 mg/dL and the ethanol extract of matoa leaves had the potential to regenerate pancreatic cells in streptozotocin-induced male white rats of 0. 6±0.54